THE EFFECT OF MERGERS AND ACQUISITIONS ON FINANCIAL PERFORMANCE OF COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - Mamahit, Bonaventura L. A.; Pangemanan, Sifrid S.; Tulung, Joy E. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: General elections and government policies are affecting the company that conducted M&A in Indonesia. Furthermore, financial performance is observed to analyze the impact on M&A companies. The ratio that used in this research is a liquidity ratio that is Current Ratio as the dependent variable and profitability ratio that is Return on Equity, Return on Assets, Operating Profit Margin, Gross Profit Margin, and Net Profit Margin as the independent variable. The data is taken from the company's annual report and the statistical analysis tools used in this research are Stata. To observe the changes in financial performance value the Panel Data Regression is used in this research, for before and after M&A the Wilcoxon Signed Rank Test has been conducted in this research. As a result of the statistical analysis this research has determined the company's financial performance through years and within the period from before and after the company conducted M&A. The result of this research indicates that the average value of the profitability ratios on the company performance before M&A is greater than the period after M&A. Based on the Wilcoxon signed-rank test it is only GPM and CR that have no significant influence on the before and after the company conducted M&A Keywords: financial performance, mergers and acquisitions, companies, profitability ratio, liquidity ratio.